2015
DOI: 10.1007/s00441-015-2158-z
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear efferents in developing adult and pathological conditions

Abstract: Cochlear activity is regulated by the olivo-cochlear bundle, which originates from the brainstem and projects onto the hair cells and auditory nerve fibers. Two efferent components can be distinguished: the medial and lateral olivo-cochlear efferent originating from the medial, and the lateral nuclei of the superior olivary complex. The input of the efferent systems on hair cells occurs during development and persists in the adult cochlea. Recent studies have shown that the efferent innervations are required t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 79 publications
4
33
0
Order By: Relevance
“…No studies that have observed responses of the olivocochlear efferent system in PD were found. However, OAEIE is known to reflect the functioning of the medial olivocochlear efferent system (MOES), which inhibits EHC contractile responses in the presence of competitive noise (18) and its activity mediated by cholinergic and gabaergic neurotransmitters (19) . On the other hand, cochlear responses are also influenced by the lateral olivocochlear efferent system (LOES), which has dopamine as one of its main neurotransmitters (19) .…”
Section: Discussionmentioning
confidence: 99%
“…No studies that have observed responses of the olivocochlear efferent system in PD were found. However, OAEIE is known to reflect the functioning of the medial olivocochlear efferent system (MOES), which inhibits EHC contractile responses in the presence of competitive noise (18) and its activity mediated by cholinergic and gabaergic neurotransmitters (19) . On the other hand, cochlear responses are also influenced by the lateral olivocochlear efferent system (LOES), which has dopamine as one of its main neurotransmitters (19) .…”
Section: Discussionmentioning
confidence: 99%
“…At present it is unclear how MOC or LOC synapses change with age in humans or other strains of mice. Substantial reorganization of efferent synapses may serve to minimize excitotoxic damage to auditory nerve dendrites, which could prevent accumulated damage from everyday noise exposures (Nouvian et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…They may have continued functioning, for example, by their input on auditory afferents, or by transient innervation of IHC (cf. Nouvian et al, ). This does, however, not rule out any early short‐or long‐term disturbances elicited by noise.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that, under these conditions, afferent synaptic contacts are lost and that efferent neurons form (transient) synapses with IHC (cf. Nouvian et al, ).…”
Section: Discussionmentioning
confidence: 99%